Chirality conferral enables the observation of hyper-Raman optical activity - Jones, Robin; Kerr, John F.; Kwon, Hyunah; Clowes, Samuel R.; Ji, Ruidong; Petronijevic, Emilija; Zhang, Liwu; Pantoş, G. Dan; Smith, Brian; Batten, Tim; Fischer, Peer; Wolverson, Daniel; et al. (Nature photonics, 2024)
Chirality conferral is fundamental for understanding the origin of life, and it is of direct importance for synthesizing new pharmaceuticals in the face of growing antibiotic resistance. Human-made, self-assembling nanostructures replicate the biological chirality conferral processes utilizing covalent and non-covalent bonds. However, chirality conferral from one form of matter to another via electromagnetic fields is more subtle and less explored. Here we report chirality conferral between gold nanohelices and achiral molecules (crystal violet). This conferral enables the experimental observation of a physical effect predicted in 1979 - hyper-Raman optical activity. To benefit from Fermi’s golden rule, the chirality conferral system was designed as doubly resonant, with the nanohelices and molecules resonating at the fundamental frequency and at the second-harmonic, respectively. We provide a theoretical framework for our results that expands the original mathematical formalism to include surface-enhanced hyper-Raman scattering and the chirality conferral process. Our results demonstrate that field-driven chirality conferral mechanisms are opening up entire fields of research, as exemplified by the discovery of a physical phenomenon.
Gesehen am 04.02.2025